Efficacy and Safety of Apixaban Versus Warfarin in Patients With Atrial Fibrillation and Extremes in Body Weight: Insights From the ARISTOTLE Trial. Issue 20 (14th May 2019) - Hohnloser, Stefan H.; Fudim, Marat; Alexander, John H.; Wojdyla, Daniel M.; Ezekowitz, Justin A.; Hanna, Michael; Atar, Dan; Hijazi, Ziad; Bahit, M. Cecilia; Al-Khatib, Sana M.; Lopez-Sendon, Jose Luis; Wallentin, Lars; et al.
Abstract : Background: Guidelines caution against the use of non–vitamin K antagonist oral anticoagulants in patients with extremely high (>120 kg) or low (⩽60 kg) body weight because of a lack of data in these populations. Methods: In a post hoc analysis of ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation; n=18 201), a randomized trial comparing apixaban with warfarin for the prevention of stroke in patients with atrial fibrillation, we estimated the randomized treatment effect (apixaban versus warfarin) stratified by body weight (⩽60, >60–120, >120 kg) using a Cox regression model and tested the interaction between body weight and randomized treatment. The primary efficacy and safety outcomes were stroke or systemic embolism and major bleeding. Results: Of the 18 139 patients with available weight and outcomes data, 1985 (10.9%) were in the low-weight group (⩽60 kg), 15 172 (83.6%) were in the midrange weight group (>60–120 kg), and 982 (5.4%) were in the high-weight group (>120 kg). The treatment effect of apixaban versus warfarin for the efficacy outcomes of stroke/systemic embolism, all-cause death, or myocardial infarction was consistent across the weight spectrum (interaction P value>0.05). For major bleeding, apixaban had a better safety profile than warfarin in all weight categories and even showed a greater relative risk reduction in patients in the low (⩽60 kg; HR, 0.55; 95% CI, 0.36–0.82) and midrange (>60–120 kg) weight groups (HR, 0.71; 95% CI, 0.61–0.83; interaction P value=0.016). Conclusions: Our findings provide evidence that apixaban is efficacious and safe across the spectrum of weight, including in low- (⩽60 kg) and high-weight patients (>120 kg). The superiority on efficacy and safety outcomes of apixaban compared with warfarin persists across weight groups, with even greater reductions in major bleeding in patients with atrial fibrillation with low to normal weight as compared with high weight. The superiority of apixaban over warfarin in regard to efficacy and safety for stroke prevention seems to be similar in patients with atrial fibrillation across the spectrum of weight, including in low- and very high–weight patients. Thus, apixaban appears to be appropriate for patients with atrial fibrillation irrespective of body weight. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00412984. Abstract : Supplemental Digital Content is available in the text.